A Sordid God: Melville, Dante, and the Voyage to Hell - Kenngott, Christine Maria (The Ohio State University, 2014)
In my thesis I will examine the relationship between Herman Melville’s Moby-Dick and Dante’s Inferno, suggesting the latter as a possible inspiration for the format of Moby-Dick. I will begin by discussing the influence of Greek mythology and the reemergence of Dante in nineteenth-century America. Once the historical scene is set, I will detail the similarities between the structure and characters of the two texts. I will suggest that Ishmael plays a role similar to that of Dante in the Inferno. I will also present Queequeg as a possible Virgil, the virtuous pagan who has led Ishmael through his katabasis but cannot follow him in the journey out of hell. I will then proceed to illustrate the ways in which Ahab embodies the descent into the underworld by committing each of the sins described in the Inferno and figuratively crossing each of the rivers that separate it from the world of the living—the rivers of woe, lamentation, fire, forgetfulness, and hate. After each section, I will present a character who, when faced with the same choices as Ahab, has taken the opposite course. Ahab believes that it is his fate to destroy the White Whale. I will argue that the characters whose actions stand in opposition to his own are using the Christian idea of free will to take charge of their lives and responsibility for their actions, counteracting the pagan belief in fate. By showing each of these characters in opposition to Ahab, I wish to suggest the role of free will over blind fate in the novel. I will also argue that Dante, through his incorporation of pagan characters into his Christian hell, has made a similar statement about free will vs. fate, which we can use to help better understand the consequences of Ahab’s sins. Scholars have identified structural similarities between Melville’s works and Dante’s Inferno, most notably in Pierre, “The Tartarus of Maids,” and “The Encantadas.” I have not, on the other hand, found much scholarship connecting the Inferno with Moby-Dick. I believe there is much to be learned about the characters, the structure of the novel, and the role of free will vs. fate from such an analysis. No embargo Academic Major: English